Incorporating RDA Outputs in the Design of a European Research Infrastructure for Natural Science Collections. (14th December 2020) - Islam, Sharif; Hardisty, Alex; Addink, Wouter; Weiland, Claus; Glöckler, Falko
To support future research based on natural sciences collection data, DiSSCo (Distributed System of Scientific Collections) – the European Research Infrastructure for Natural Science Collections – adopts Digital Object Architecture as the basis for its planned data infrastructure. Using the outputs of one Research Data Alliance (RDA) interest group (IG) and five working groups (WGs) we show how RDA recommendations and supporting documents have been applied to the various stages of the DiSSCo data lifecycle.